De la pluma a las letras de molde : análisis de manuscritos y "editiones principes" de la Edad Moderna - Paniagua Pérez, Jesús; Testi, Dario (De Gruyter, 2023)
Ecdotics, or the study of text editions, is an essential part of Hispanic humanism. In a pluridisciplinary approach, the volume gathers contributions by scholars from Italy, Spain and Colombia about the vicissitudes of Hispanic books and manuscripts between the 16th and 19th centuries. They discuss, among other topics, historiographical sources, lexical questions, cartographic analysis and poetry analysis.